The quality of fermented goat milk produced by Pediococcus acidilactici BK01 on refrigerator temperature - sri Melia; Indri Juliyarsi; Yulianti Fitri Kurnia; Yudha Endra Pratama; Dhiva Rezzy Pratama (Society for Indonesian Biodiversity, 2020)
Abstract. Melia S, Juliyarsi I, Kurnia YF, Pratama YE, Pratama DR. 2020. The quality of fermented goat milk produced by Pediococcus acidilactici BK01 on refrigerator temperature. Biodiversitas 21: 4591-4596. This research aimed to determine the quality of chemical and microbiological milk of goats fermented with Pediococcus acidilactici BK01 with the storage time on refrigerator temperature. The method used is the experimental method of Completely Randomized Design with five times the treatment of goat milk fermentation at the refrigerator temperature is over 0, 7, 14, 21, and 28 days with four repetitions. The results showed long-lasting storage of real effect (P < 0.05) on water content, pH, titratable acid, total lactic acid bacteria, and total plate count, but no noticeable effect (P > 0.05) on the protein levels and milk fat fermentation during the resulting storage. The value of moisture content during storage ranges between 85.88-84.92%, pH 4.48-4.28 , 3.69-3.49% fat content, 3.53-3.58% protein content, as well as the count of titratable acid ranging from 1.52-1.73%. The whole colonies of lactic acid bacteria reached between 9.106 log CFU/mL to 10.376 log CFU/mL, and the total plate count (TPC) value during storage experienced an increase from 2.653 log CFU/mL to 4.012 log CFU/mL. Based on the results of the study can be concluded that the milk of goat fermentation with P. acidilactici BK01 can maintain quality until the retention period of 28 days with the viability of lactic acid bacteria that meet the category as probiotics and still liked by the consumer.